Evaluating the Cu and Zn status of various rice soils of Peninsular Malaysia - Babar, Saima Kalsoom; Yusop, Mohd Khanif; Abd. Wahid, Samsuri (Universiti Putra Malaysia Press, 2016)
Malaysia is taking efforts to be self.sufficient in rice production. However, the country is facing low availability of Cu and Zn in its soils. Even though these elements are required in small quantities for normal plant growth, their role in maximising yield is very impressive. The present study was conducted to assess the micronutrient Cu and Zn contents in selected paddy soils of Malaysia. Investigations carried out showed that marine alluvium [Guar, Sedaka, Keranji, Kuala Kedah, Kangkong, Sedu, Rotan and Kundur (Kedah)] and reverine alluvium; [Chempaka, Lubok Itek, Lating, Batu Hitam and Machang soil series (Kelantan)] were low in Cu and Zn contents. All soils were acidic in nature, with their pH values ranging from 4.3 to 6.5. Based on the results, extractable Cu and Zn concentration of soil varied within the range of 0.09.1.70 and 0.51.2.10 mg kg-1 in the soil series of Kuala Kedah and LubukItek, respectively. It was manifested that the micronutrient contents were below the critical level (Cu 0.1.1.0 mg kg-1 and Zn 0.5.3.0 mg kg-1)according to the method of extracting analysis; Mehlich.I. The sampling depth has shown a variation and the subsurface soil sampling exhibited lesser Cu and Zn contents as compared to the surface soil sampling. Findings of the research indicate that micronutrient deficiency occurs in the main rice regions of Malaysia, and this can be corrected by applying micronutrient fertiliser.